The factors driving sociology students participation in volunteer work "A field study of a sample of university students in the Faculty of Arts, Tishreen University Department of Sociology" - اسماعيل, رندا (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
Voluntary work in its social and humanitarian approach represents a civilized behavior that societies and civilizations have promoted since ancient times, and it is a symbol of solidarity and cooperation between members of society within its various institutions. There is no doubt that volunteering is of great and significant importance that positively affects the life of the individual, family and society. And at all economic, social and development levels, where volunteer work represents a practical embodiment of the principle of social solidarity, as it is a set of humanitarian, charitable and societal actions. Young people constitute a distinct category in any human society for personal and objective reasons, which is summarized in their presence in all layers of society and all classes of society. This group has an essential feature as it is one of the sources of social change, and they are the qualified force, according to work and knowledge, culture and behavior to advance the responsibilities of the sons of society, because their distinct characteristics save time and push the development process forward.